Examining the relationships between roles and status salience among military and civilian fathers post-divorce - Zimmermann, McKenzie Leigh (Kansas State University, 2021)
Since the early 1960s, most research about fathers has focused on the role that fathers have in parenting partnerships with two common roles being provider and disciplinarian. Today, research on fathers has expanded to include constructs such as father involvement, engagement, their identity, and their roles in the coparenting partnership. Using structural identity theory and data from 261 military and civilian participants who have experienced a divorce or separation, I examined the differences in the ways that military and civilian fathers perceived their father status and associated roles (authority figure, caregiver, financial provider, and teacher) after a divorce or separation. This study also examined the relationship between the salience of roles and statuses and other covariates such as coparenting quality behaviors and father involvement. Results indicate differences between military and civilian fathers on the basis of status salience and coparenting quality behaviors. For civilian fathers, their most salient roles were caregiver and teacher, whereas military fathers’ most salient roles were authority figure and financial provider. Further, father involvement among military and civilian fathers was similar based on t-tests, but different in the regression models. Military affiliation and status salience were significant predictors of father involvement, as were physical custody and specific roles. As for coparenting quality behaviors, ethnicity, and legal and physical custody were significant predictors among all four role salience variables. Military affiliation was consistently negatively associated with coparenting behaviors and status salience was the strongest predictor variable among all four roles’ salience models on the basis of coparenting quality behaviors. Findings can help divorce education program facilitators create programs that are more tailored to fathers’ roles within their coparenting relationship. This study can also assist policymakers to create more programs dedicated to military fathers and their involvement and coparenting behaviors.
Keywords: Fathers; Military; Coparenting; Father involvement; Father roles